IMPLEMENTASI PROGRAM INDONESIA SEHAT DENGAN PENDEKATAN KELUARGA (PIS-PK) PADA MASA PANDEMI - Feni Sulistyawati; Ni Luh Purnama Yanti (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2022)
In achieving the highest degree of public health, the Public Health Center organizes public health efforts (UKM) and individual health efforts (UKP) by prioritizing promotive and preventive efforts. UKP and UKM are implemented through Public Health Center program. One of Public Health Center programs is the Healthy Indonesia Program with a Family Approach (PIS-PK). In its implementation, the function between UKP and UKM must be balanced in order to achieve an increase in the degree of public health. The current Covid-19 pandemic has also affected the implementation of the program at the Public Health Center. This study aims to determine the implementation of the Healthy Indonesia Program with a Family Approach (PIS-PK) during the Covid-19 pandemic at the Kediri III Health Center. This study uses a qualitative method with a case study approach. The sample selection used purposive sampling, namely an informant. Data collection based on primary and secondary data was carried out by means of interviews and document review. Data analysis using bottleneck analysis from Tanahashi. There are limited facilities and infrastructure due to the absence of internal health center policies related to PIS-PK, equipment and also the budget for PIS-PK implementation. In addition, the achievement of PIS-PK indicators is still low, especially on indicators of TB treatment, hypertension treatment and also family members who do not smoke. Another obstacle is related to the achievement of Healthy Family Index which is still classified as an unhealthy family. There are obstacles in terms of supply and demand. It is hoped that there will be good coordination and communication between the Health Office and the Public Health Center. The Public Health Center should develop internal policies related to the implementation of PIS-PK.